A distributed monitoring scheme for a fleet of UAV flying drones. (19th October 2022) - Nouasri, Amine; Riahla, Mohamed Amine
In this paper, we present a solution that would allow members of a unmanned Arial vehicles (UAV) drone fleet to cooperate with each other in order to monitor the network regarding incidents that could compromise security or impact service continuity during their mission. The proposed work implements a scheme to allow each drone to monitor the activity of immediate neighbours without a central control authority, and share that information. This is in order to decide of an action in case of a security incident or a degradation of their service has occurred. The purpose is to allow the network to be resilient and adopt itself to insure service continuity. The method we used allow the detection of incidents without the use of complex security and routing solutions, or the need to communicate back and forth with a central control authority. Our method uses four parameters to insure service continuity in the network: link quality, forwarding rate, checksum rate and mobility coordinates. This is to allow the detection of multiple incidents using the same scheme.